Consumer responses to time-based sales messages. (March 2023) - Yang, Bi; Li, Shanshi; Chen, Zhenyu; Mattila, Anna S.
Abstract: Although time-based sales messages (e.g., booked X times in the last Y hours) are frequently employed in the travel industry, their effectiveness has not been systematically examined in previous research. To fill this gap, we compare two types of sales messages: large total sales in a long term vs. large hourly sales in a short term (e.g., 72 times/24 h vs. 48 times/6 h). Our results indicate that most people tend to be more persuaded by hourly sales and that such a tendency is negatively related to individuals' experiential thinking style. We also find that displaying temporal information before sales volume increases the power of hourly sales among people low in experiential thinking style. Highlights: Two types of sales messages (large total sales vs. large hourly sales) are studied. Most people tend to be more persuaded by hourly sales. Such a tendency is negatively related to individuals' experiential thinking style. Presentation order of information influences the power of hourly sales.